Microbiome Evolution of Brewer’s Spent Grain and Spent Coffee Ground Solid Sidestreams Under Industrial Storage Conditions - Christian Hermansen; Qi Kang Chong; Sherilyn Ho; Federica Natali; Melanie Weingarten; Eric Charles Peterson (Applied Sciences)
Brewer’s spent grain (BSG) and spent coffee ground (SCG) are solid sidestreams from beverage production increasingly being upcycled into food, feed and other value-added products. These solid sidestreams are prone to microbial spoilage, negatively impacting their upcycling potential. Three samples each of BSG and SCG were obtained from generators and recycling facilities in Singapore, and their chemical, elemental, and microbial composition was characterized. The spoilage mechanisms were investigated during storage under anaerobic and aerobic conditions. Bacterial loads of sidestreams were low from craft brewery and café sources (<1 and 3.53 ± 0.03 log10 CFU/g) and high from recycling facilities (>6 log10 CFU/g). The microbiome of BSG from recycling facilities was dominated by Bacilli, and B. coagulans was identified as the most prevalent species. SCG from recycling facilities was dominated by lactic acid bacteria, with L. panis being the most prevalent species. Storage up to 14 days under anaerobic conditions led to further bacterial proliferation mainly by Bacilli, lactic acid bacteria, and acetic acid bacteria, while aerobic storage led to extensive fungal contamination, including potential aflatoxin-producing Aspergillus flavus. The results shed light on the spoilage mechanisms, while highlighting the short shelf-life and food safety risks of BSG and SCG to inform valorization strategies.